Inter-Sectorial Linkage of Economic Sectors and Their Contribution to Economic Growth: A Time Series Evidence from Ethiopia and China - Gessesse, Abrham Tezera; Xungang, Zheng; Ge, He (American Journal of Trade and Policy, 2018)
Purpose: The aim of this paper is to investigate the inter-sectorial linkage of economic sectors and their contribution to the economic growth using time series data from 1978-2014 and 1992-2014.Design/methodology/approach: This study employed a Johansen cointegration test and Ordinary Least Square (OLS) model.Findings: The Johansen cointegration and multiple regression results indicate that all economic sectors have strong, positive and significant long-run and short-run relationship with economic growth during the study period in both countries. The result revealed that MNF giant is an engine for Chinese economic growth while agriculture took the lion-share for Ethiopian economy. The MNF has bi-directional Granger cause with economic growth, agriculture and SRV for China, while GDP and AGR are the only bi-directional Granger causes variables for Ethiopia.Implications: Therefore, from a policy perspective, Ethiopian policymakers need to formulate agro-processing industries to ensure the transformation of the AGR to the MNF as well as maintain inter-sectorial linkage and sustain the country’s economic growth.
Keywords: Economic sectors; Economic growth; Granger cause; Ethiopia; China